Role of Artificial Intelligence in Indian Insurance Industry: Challenges and Opportunities from Sustainability Perspectives (Journal of Informatics Education and Research, 2023)
The present study explores the use of Artificial Intelligence (AI) in the insurance industry in Andhra Pradesh, emphasizing the prospects and obstacles from a sustainability standpoint. An employee sample of 270 in the insurance industry was polled to learn more about how they saw the use of AI, how it affected sustainability practices, and what possibilities and difficulties it brought with it. The study uses a strong research technique that includes detailed data analysis, survey data gathering, and demographic profiling. The results show a varied adoption landscape for AI, with some organizations actively using the technology and others make plans for future integration. Opportunities like data integration and automation are noted with challenges like financing restrictions and a lack of technological competence. Sustainability techniques are recognized, highlighting the industry's dedication to ethical business practices. Examples of these activities include sustainable data management and effective resource consumption. With a sophisticated knowledge of the intricate link between AI adoption and sustainability within the Andhra Pradesh insurance business, the research closes with important recommendations for policymakers and industry stakeholders.